REPRESENTASI STEREOTIP PEREMPUAN DALAM FILM 3 SRIKANDI MELALUI ANALISIS SEMIOTIKA ROLAND BARTHES - Karina Puji Lestari; Ariyanti, Vega; Nor Kholisoh, Siti; Setiyani, Dewi; Fatah, Ahmad (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
The film 3 Srikandi tells the true story of the struggle of three Indonesian female archery athletes at the Seoul Olympics in 2988, this film is an important example in the representation of stereotypes of women in the socio-cultural life of the Indonesian people which is packaged naturally in national cinema. The purpose of this study is to find out the representation of stereotypes of women reflected in the film 3 Srikandi through Roland Barthes' semiotic analysis. The type of research used is qualitative descriptive research with a semiotic analysis approach method. The research data is in the form of fragments of sentences, dialogues and scene images that show the stereotypes of women in the film 3 Srikandi. The results of the study show that the film 3 Srikandi not only shows the story of the struggle of the three main characters but, on the other hand, it also shows many stereotypes of women who are still thriving in the socio-cultural life of Indonesian society, such as women often feel dilemmas when choosing between their careers and personal lives, women are figures who pay attention to physical beauty, women are figures who are synonymous with tenderness but On the other hand, they are able to do hard work like men, women are strong figures in facing any situation, women are figures who have high dedication and never give up if they have a dream, and women as figures who provide warmth and emotional support to fellow women.